Impact of Acute Physical Activity on Children's Divergent and Convergent Thinking: The Mediating Role of a Low Body Mass Index. Issue 4 (August 2019) - Bollimbala, Ashish; James, P. S.; Ganguli, Shirshendu
While prior studies have examined the positive influence of physical activity (PA) programs on children's creative potential, they have not explored the mediating roles of psychological and physiological variables. In this study, we investigated the impact of a single dance session as a form of PA on two indicators of creative potential—divergent and convergent thinking, each of which adopts a different cognitive pathway. We also investigated the influence of a physiological condition, low body mass index (BMI), on the relation between PA and creative potential. This was a randomized controlled experiment involving 34 school children randomly assigned to either the dance intervention or a sedentary group based on their BMI profile. We measured the children's divergent and convergent thinking at pre- and post-intervention time points. Following this single PA session, we found a significant difference between divergent and convergent thinking abilities in treatment group participants with normal BMI levels and participants in the control group, but there was no difference between low BMI level treatment group participants and those in the control group. This study supported hypothesized boundary conditions for executive function improvements from PA and suggests a need for a holistic approach (involving both proper nourishment and PA) in order to facilitate improved creativity in children.